2010
DOI: 10.1073/pnas.0907585107
|View full text |Cite
|
Sign up to set email alerts
|

Myosin complexed with ADP and blebbistatin reversibly adopts a conformation resembling the start point of the working stroke

Abstract: The powerstroke of the myosin motor is the basis of cell division and bodily movement, but has eluded empirical description due to the short lifetime and low abundance of intermediates during force generation. To gain insight into this process, we used wellestablished single-tryptophan and pyrene fluorescent sensors and electron microscopy to characterize the structural and kinetic properties of myosin complexed with ADP and blebbistatin, a widely used inhibitor. We found that blebbistatin does not weaken the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
47
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 32 publications
3
47
1
Order By: Relevance
“…Crystal structures of myosin bound by blebbistatin with ADP and vanadate (26) or ADP and vanadate without blebbistatin (27) show switch-2 in a closed conformation. Furthermore, spectroscopic studies suggest that blebbistatin (28) and vanadate (13) stabilize the closed state of switch-2 in the presence of ADP without P i or P i analogs. Thus, switch-2 is likely predominantly closed in the presence of blebbistatin and vanadate, and because actin-induced LCD rotation is inhibited by both, we infer that the power stroke requires acceleration of switch-2 opening just as predicted by previous studies (5,14) and by crystallographic models (4,16).…”
Section: Discussionmentioning
confidence: 99%
“…Crystal structures of myosin bound by blebbistatin with ADP and vanadate (26) or ADP and vanadate without blebbistatin (27) show switch-2 in a closed conformation. Furthermore, spectroscopic studies suggest that blebbistatin (28) and vanadate (13) stabilize the closed state of switch-2 in the presence of ADP without P i or P i analogs. Thus, switch-2 is likely predominantly closed in the presence of blebbistatin and vanadate, and because actin-induced LCD rotation is inhibited by both, we infer that the power stroke requires acceleration of switch-2 opening just as predicted by previous studies (5,14) and by crystallographic models (4,16).…”
Section: Discussionmentioning
confidence: 99%
“…2,3-butanedione monoxime (BDM), N -benzyl-p-toluenesulphonamide (BTS) and blebbistatin are inhibitors of class-2 myosins [193198]. The inhibitory effect of the low-affinity compound BDM is skeletal-muscle myosin-2 specific (IC 50 ~5 mM) and associated with the allosteric inhibition of P i release [197].…”
Section: Regulation By Small Moleculesmentioning
confidence: 99%
“…2). The M·ADP·blebbistatin complex has a very low actin affinity and adopts a structural state that resembles the starting point of the powerstroke [193, 196, 200]. Structural studies show the blebbistatin binding site in the apex of the myosin cleft [201].…”
Section: Regulation By Small Moleculesmentioning
confidence: 99%
“…For example, crosslinking of myosin with azidoblebbistatin in different nucleotide-and actin-bound states may stabilize important intermediates of force generation. Such a possibility is substantiated by our recent finding that the complex of myosin with ADP and blebbistatin adopts a previously inaccessible structural state resembling the start point of the powerstroke (13). In this as well as many other cases, the relatively low affinity of the ligands for the enzyme is the most severe technical hurdle in the way of detailed structural characterization, which can be overcome by covalent crosslinking to azidoblebbistatin.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, we recently showed that myosin populates a previously inaccessible conformational state when bound to ADP and blebbistatin. This conformational state, characterized by a primed lever and high actin affinity, resembles the start point of the powerstroke (13).…”
mentioning
confidence: 91%